Torsion of a seminoma in an intrascrotal testis: A case report and review of the literature - Gondo, Tatsuo (Canadian Medical Association, 2013)
An intrascrotal testicular torsion with malignant testicular tumour is extremely rare. We report a case of a 26-year-old male who was diagnosed with testicular torsion by magnetic resonance imaging and with testicular seminoma after orchiectomy. Through this case, we found that if the possibility of testicular torsion remains during the diagnosis of acute scrotum cases, additional examination adding to colour Doppler sonography should be performed. Furthermore, we should be aware of the possibility of testicular tumours during the diagnosis and treatment of acute scrotums. If the affected testis is preserved in the treatment of testicular torsion, a postoperative examination by ultrasound and/or tumour markers for the remaining testis is essential to confirm the absence of testicular tumour.